A new Coelomomyces pathogenic to mosquitoes in Costa Rica - Lichtwardt, Robert W; Gómez, Juan Diego (Revista de Biología Tropical, 1993)
A new species of fungus belonging to the lethal gmus Coelomomyces. C. neolropicus, is described and illustrated. It was found parasitizing larvae of two species of Culicidae, Culexpilosus and Aedes sp., in a lowland tropical wet rorest swamp in northeast Costa Rica.